Hemodynamic and respiratory effects of pneumoperitoneum and PEEP during laparoscopic pelvic lymphadenectomy in dogs - Luz, C. M.; Polarz, Heinrich; Böhrer, Hubert; Hundt, Guido; Dörsam, Joachim; Martin, Eike (Surgical endoscopy and other interventional techniques, 1994)
Extended laparoscopic operations are being performed increasingly in high-risk patients. To assess the effects of increased intraabdominal pressure (IAP) and positive end-expiratory pressure (PEEP) on the hemodynamic and respiratory system during extended procedures a carbon dioxide pneumoperitoneum was artificially induced in 10 dogs undergoing laparoscopic pelvic lymphadenectomy. An increase in IAP up to 15 mmHg had no negative effect on the cardiovascular system. However, the combination of an increased IAP (10-15 mmHg) with PEEP (8 cmH2O) markedly depressed the hemodynamic variables. Measurement of arterial carbon dioxide and fractional end-tidal carbon dioxide revealed significant CO2 retention. We conclude from the results that laparoscopic pelvic lymphadenectomy should be performed in high-risk patients only under general anesthesia with expanded cardiopulmonary monitoring.